"No pain, No gain" still true with immunotherapy: When the finger shows the moon, look at the moon!. (July 2018) - Milano, G.; Innocenti, F.; Lacarelle, B.; Ciccolini, J.
Graphical abstract: Highlights: For many categories of anticancer drugs toxic patients are those also presenting a response to treatment. This review investigates the molecular and pharmacokinetics explanations sustaining this relationship. Possibilities are offered for an optimal therapeutic strategy based on dose increasing up to reach toxicity. Abstract: There is a rising evidence that the proverbial statement "No pain, No gain" first coined at the light of pioneering clinical experiences with canonical chemotherapy still holds true in the era of modern treatments of cancer. This close relationship between the occurrence of specific drug-related toxicity and treatment outcome has been confirmed since then with a large variety of treatments, ranging from cytotoxics, hormonotherapy, targeted therapy and much interestingly even with the latest immune checkpoint inhibitors. In the current context of precision medicine, and along with the constant quest for identifying predictive biomarkers, close monitoring of treatment-related toxicities could therefore be convenient to help predicting therapeutic response, but presents several caveats. The purpose of this review is to briefly describe these relationships across the different treatments, to comment on possible underlying mechanisms and to comment on possible strategies aiming at exploiting this relationship while keeping the maximal safety ensured in patients with cancer. In particular, this review will investigate on how drug exposure along with germinal and somatic genetic issues does impact on the "No Pain, No Gain" aphorism, and why the temptation to use treatment-related toxicities as a cheap and convenient way to predict clinical outcome or to adapt dosing should be resisted. We do advocate instead for developing comprehensive genomic support along with extensive biomathematical modeling to better customize dosing and shift towards a new "No Pain, Maximal Gain" paradigm.